IMPLEMENTATION OF TAX COLLECTION TO INCREASE INDIVIDUAL INCOME TAX REVENUE: IMPLEMENTATION OF TAX COLLECTION TO INCREASE INDIVIDUAL INCOME TAX REVENUE - Endang Susilawati; Asep Mulyana (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2023)
Â This study aims to determine the implementation of taxcollection to increase personal income tax revenue whether there is abig effect after billing individualsâ€™ domestic private person. Taxeshave a very large role in generating domestic cash receipts in order torealize continuity and increase in national development. The methodused in this research is a quantitative method with a descriptiveapproach and the data used is secondary data. The results of the studyshow that partially Billing does not have a significant effect onIndividual Income Tax Receipts. Keywords: Implementation of Tax Collection, Increasing IndividualIncome Tax Revenue